Heat and mass transmission of an Oldroyd B nanofuid fow through a stratifed medium with swimming of motile gyrotactic microorganisms and nanoparticles (2020)
This paper focuses on the research of motile microorganism rates in the bioconvective Oldroyd-B nanoliquid fow over a vertical stretching sheet with mixed convection and inclined magnetic feld. Additionally, interesting characteristics of thermophoresis, Brownian motion, viscous dissipation, Joule heating, and stratifcation are examined. Similarity transformations are employed to reduce the mathematical model to higher-order ODE. The convergent serious solution is applied to solve the nonlinear diferential system. The analysis of temperature, velocity, motile microorganisms’ density, and nanoparticle concentration are represented through graphs. Local Nusselt number, density number of motile microorganisms, and Sherwood number are examined via contour plots.